Effect of H-bonding on network junction and macroscopic elastomer properties in photocured polyacrylate films. (1st February 2022) - Wu, Bing; Chassé, Walter; Heise, Andreas; Kentgens, Arno P. M.; Brougham, Dermot F.; Litvinov, Victor M.
Abstract : Two series of polyacrylate films with different H-bonding capable monoacrylate copolymers were synthesized by UV-initiated photo-polymerization. Abstract : Two series of polyacrylate films with different H-bonding capable monoacrylate copolymers were synthesized by UV-initiated photo-polymerization. Detailed IR analyses on cured samples show that networks made from structurally distinguishable mono-acrylate have significantly different extent of H-bonded monoacrylate present. We found that this is induced by differences in the relative reaction rate between homo-polymerization and copolymerization of the relevant monoacrylates and crosslinker (PEGDA). Although 'pre-organization' of H-bond capable monoacrylates was observed for those tested formulations prior to crosslinking, which should significantly increase the homo-polymerization rate, it was found that the co-polymerization rate was also significantly increased. Furthermore, DQ NMR analyses on these networks pinpoints the presence of H-bonding clusters, which decreases mobility of chain segments near the H-bonding functional groups in the monoacrylate sidechains (dangling chain segments of monoacrylate). However, the overall network topology does not alter significantly upon forming H-bonding clusters in the monoacrylate sidechains. Finally it was also found that larger H-bonding clusters increase the apparent network junction functionality. These findings are discussed in the context of utilizing the H-bonding capable monoacrylates to tailor the microscopic topological properties as well as macroscopic physical properties of photocured polyacrylate polymer films.